Edukasi Pencegahan Covid-19 Melalui Media Poster dan Spanduk Pada Warga Kelurahan Panji Kecamatan Tenggarong - Susanti, Rahmi; Erika, Tahsya (LPPPM STAI Darul Hikmah Bangkalan, 2021)
Coronavirus is a disease that causes respiratory infections. Like other respiratory illnesses, COVID-19 can cause mild symptoms including runny nose, sore throat, cough and fever. Print media is one of the educational media to find out the dangers and prevention of COVID-19 transmission and access to health information. The activities of distributing posters and installing banners are aimed at increasing public awareness about the dangers and prevention of COVID-19 transmission and access to health information. This activity was in the form of distributing posters directly to residents' homes and installing banners in the Gang Nidatul Khair RT area. 12 Panji Village, Tenggarong District, Kutai Kartanegara Regency on November 28, 2020 with 15 posters and 1 banner about the dangers and prevention of COVID-19. 19 and access to health information. This activity has received a pretty good reception by the community as shown by the information presented, it is hoped that it can increase knowledge and increase public awareness about the dangers and importance of preventing COVID-19 and access to health information.